The origin of the C-genome and cytoplasm of Avena polyploids - Nikoloudakis, Nikolaos; Katsiotis, Andreas (My University, 2008)
The contribution of C-genome diploid species to the evolution of polyploid oats was studied using C-genome ITS-specific primers. SCAR analysis among Avena accessions confirmed the presence of C-genome ITS1-5.8S-ITS2 sequences in the genome of AACC and AACCDD polyploids. In situ hybridization and screening of more than a thousand rRNA clones in Avena polyploid species containing the C-genome revealed substantial C-genome rRNA sequence elimination. C-genome clones sequenced and Maximum Likelihood Parsimony analysis revealed close proximity to Avena ventricosa ITS1-5.8S-ITS2 sequences, providing strong evidence of the latter's active role in the evolution of tetraploid and hexaploid oats. In addition, cloning and sequencing of the chloroplastic trnL intron among the most representative Avena species verified the maternal origin of A-genome for the AACC interspecific hybrid formation, which was the genetic bridge for the establishment of cultivated hexaploid oats.
Keywords: Oats; Avena sativa; Crown rust